Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.jnoncrysol.2015.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal annealing on the blue luminescence of amorphous silicon oxycarbide films

Abstract: Amorphous silicon oxycarbide (a-SiC x O y ) films that displayed blue luminescence were fabricated using very high frequency plasma-enhanced chemical vapor deposition (VHF-PECVD) at a temperature of 250 C. The effects of thermal annealing on the photoluminescence (PL) were investigated. Thermal annealing at 600 °C resulted in a remarkable enhancement in the blue PL, which was clearly observed with the naked eyes in a bright room. The blue PL featured an excitation wavelength independent recombination dynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…In addition, the SiC x O y matrix can also be used as donor that contributes to the light emission of Eu 2+ ions via energy transfer [22]. So far, defect states, such as C-related oxygen vacancies (C-NOVs), Si-NOVs, and Si-related oxygen deficiency centers, have been proposed to demonstrate the PL mechanism in SiC x O y [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the SiC x O y matrix can also be used as donor that contributes to the light emission of Eu 2+ ions via energy transfer [22]. So far, defect states, such as C-related oxygen vacancies (C-NOVs), Si-NOVs, and Si-related oxygen deficiency centers, have been proposed to demonstrate the PL mechanism in SiC x O y [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…SiC x O y materials are a promising platform to realise direct white light emission because of their potential for desirable chromaticity and wide tuneable optical bandgaps 14 , 26 , 36 38 . Compared with other techniques to prepare SiC x O y materials such as the sol–gel method 39 , 40 , C-ion implanted SiO 2 41 , chemical vapour deposition 42 , 43 and direct-current arc discharge plasma 38 , the advantage of laser irradiation method is in the efficiency of the process.…”
Section: Resultsmentioning
confidence: 99%
“…However, it has been observed the incorporation of source precursor fragments and decomposition byproducts in the deposited films, which resulted in enhanced stress levels and increased defect density, both of which affecting the optical performance of the materials and device structures. Recently, Lin et al reported the growth of amorphous SiC x O y by very high-frequency PECVD technique [ 88 ]. An extensive review on the synthesis and properties of SiC x O y films is presented in [ 89 ].…”
Section: Chemical Vapor Synthesis Of Sic Films: From Cvd To Aldmentioning
confidence: 99%